70 kVp Computed Tomography Pulmonary Angiography. Issue 1 (January 2015) - Wichmann, Julian L.; Hu, Xiaohan; Kerl, Josef M.; Schulz, Boris; Frellesen, Claudia; Bodelle, Boris; Kaup, Moritz; Scholtz, Jan-Erik; Lehnert, Thomas; Vogl, Thomas J.; Bauer, Ralf W.
<x xml:space="preserve">Abstract</x> Purpose: The purpose of the study was to evaluate 70 kVp dual-source computed tomography pulmonary angiography (CTPA) with reduced iodine load in comparison with single-source 70 and 100 kVp CTPA with standard iodine load regarding image quality and radiation dose. Materials and Methods: Three groups with 40 consecutive patients each underwent either standard single-source 100 kVp (120 mAs; group A), single-source 70 kVp (208 mAs; group B), or dual-source 70 kVp CTPA (416 mAs; group C). A volume of 70 mL of contrast material with 400 mg I/mL (groups A, B) or 300 mg I/mL (group C) was administered. Chest diameter, dose-length product, intravascular signal attenuation, image noise, signal to noise ratio (SNR), and contrast to noise ratio (CNR) were compared. Two observers rated subjective image quality regarding intravascular enhancement and image noise using 5-point scales. Results: Chest diameter and age were similar (P≥0.28) for all groups. Compared with group A, the average dose-length product was 59% lower in group B (67.3±11.8 vs. 164.7±50.6 mGy cm, P<0.001) and similar between groups A and C (167.7±41.2 mGy cm, P=0.39). Average SNR and CNR were significantly higher for group C (21.5±4.7 and 19.0±4.5, respectively) compared with groups A (18.3±3.5 and 15.8±3.4, respectively) and B (17.3±5.8 and 15.6±5.5, respectively; all Ps⩽0.001). Subjective image quality ratings regarding enhancement and noise were highest for group C (1.73±0.62 and 2.03±0.66, respectively). Conclusions: Compared with standard 100 kVp CTPA, single-source 70 kVp CTPA allows for significant radiation dose savings with comparable SNR and CNR, whereas dual-source 70 kVp CTPA results in a superior objective image quality albeit a reduction of iodine concentration.